2015
DOI: 10.1002/mar.20838
|View full text |Cite
|
Sign up to set email alerts
|

Headless: The Role of Gender and Self‐Referencing in Consumer Response to Cropped Pictures of Decorative Models

Abstract: Product pictures with “headless” decorative models, whose heads have been cropped out of the pictures, are often used in online retailing. This article reports findings from three experiments comparing attitudes for clothing displayed in pictures with cropped and uncropped male and female models, focusing on the moderating effects of consumer and model gender and the mediating effects of product self‐referencing. Results indicate that the effects on product attitudes are moderated by the gender of both models … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 55 publications
0
17
0
Order By: Relevance
“…Berg (2015) observed that consumers' attitudes were more positive for products worn by human models with a face (vs. without a face). On the other hand, Lindström et al (2016) did not find a significant difference between mannequins with vs. without a face on online purchase intention.…”
Section: Literature Review and Hypothesismentioning
confidence: 98%
See 1 more Smart Citation
“…Berg (2015) observed that consumers' attitudes were more positive for products worn by human models with a face (vs. without a face). On the other hand, Lindström et al (2016) did not find a significant difference between mannequins with vs. without a face on online purchase intention.…”
Section: Literature Review and Hypothesismentioning
confidence: 98%
“…Berg, 2015;Di et al, 2014) reported the effects of product attractiveness on consumers' behavior, so this study also investigated the role of attractiveness in the relationship among the variables mentioned earlier. The pictures evaluated are the most common ones used in e-commerce (Berg, 2015;Di et al, 2014;Yoo and Kim, 2012): flat (only the product is pictured, without other elements), mannequin (the product is pictured on a body form without a human model), human model without a face and human model with a face. Previous studies have not compared these four types of product pictures.…”
Section: Introductionmentioning
confidence: 99%
“…We hypothesize an interaction effect of emotion displays and dress color on customer tipping and employee warmth as extant research suggests that customers perceive frontline employees holistically (Aviezer et al, 2012; Berg, 2015). We argue that dress color influences the effects of positive emotion displays on marketing outcomes and that this interaction effect can be explained by fit.…”
Section: Conceptual Background and Hypothesesmentioning
confidence: 99%
“…Extant research widely neglects possible interdependencies and, by extension, the possible effects that aesthetic displays may have on the effectiveness of positive emotion displays. We question this separate consideration of both displays in research and practice as the perception of human beings is holistic (Aviezer et al, 2012; Berg, 2015) and emotion displays are not processed in isolation (for a review, see Matsumoto & Sung Hwang 2010). For example, Aviezer et al (2012) show that faces and bodies are processed as one unit and that a congruent body facilitates the interpretation of facial expressions, and Freeman et al (2011) show that perceived facial ethnicity is affected by signals from clothing.…”
Section: Introductionmentioning
confidence: 99%
“…This limitation contrasts starkly with sociological research showing that attitudes toward both sexuality and gratuitous stimuli are significantly influenced by gender, leading to noticeably different reactions (Conley, 2011; Greer & Buss, 1994; Kozak et al, 2009). Advertising literature, across the board, also provides robust empirical evidence of consumer–model gender effects in various marketing communication contexts (Berg, 2015; Eisend, 2010; Trivedi & Teichert, 2019). It has been shown that females respond differently than males to advertisements, resulting in different levels of advertising effectiveness (Moore, 2007; Teichert et al, 2018).…”
Section: Introductionmentioning
confidence: 99%